2010
DOI: 10.1007/s11596-010-0557-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated homocysteine and C-reactive protein levels independently predict worsening prognosis after stroke in Chinese patients

Abstract: Summary Increased plasma total homocysteine (tHcy) and high sensitivity C-reactive protein (hsCRP) levels are independent risk factors for cardiovascular disease. However, the predictive value of tHcy in combination with hsCRP in patients with stroke is not known. To determine the relationship between tHcy and hsCRP, we enrolled 291 patients with first-onset stroke (196 ischemic and 95 hemorrhagic). Plasma tHcy and hsCRP levels were measured and subsequent vascular events and deaths were determined over a 5-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…Youssef et al (23) study demonstrated that high total homocysteine plasma concentration was associated with increased CRP levels in cerebrovascular diseases in an association analysis of a small sample. Also, Jiangtao et al (5) demonstrated this linear association between plasma total homocysteine and CRP levels in a larger sample study on 291 Chinese patients with stroke. In a 5-year follow up study, they showed that increased total homocysteine levels are linearly associated with CRP elevation and they found that higher total homocysteine level combined with higher CRP has much more predictive value for the relative risk factor of death or new vascular events in first-onset stroke patients during long-term follow-up period.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Youssef et al (23) study demonstrated that high total homocysteine plasma concentration was associated with increased CRP levels in cerebrovascular diseases in an association analysis of a small sample. Also, Jiangtao et al (5) demonstrated this linear association between plasma total homocysteine and CRP levels in a larger sample study on 291 Chinese patients with stroke. In a 5-year follow up study, they showed that increased total homocysteine levels are linearly associated with CRP elevation and they found that higher total homocysteine level combined with higher CRP has much more predictive value for the relative risk factor of death or new vascular events in first-onset stroke patients during long-term follow-up period.…”
Section: Discussionmentioning
confidence: 78%
“…In a 5-year follow up study, they showed that increased total homocysteine levels are linearly associated with CRP elevation and they found that higher total homocysteine level combined with higher CRP has much more predictive value for the relative risk factor of death or new vascular events in first-onset stroke patients during long-term follow-up period. They also identified that the relative risk factor of death or new vascular events was 4.67 in patients with high homocysteine and CRP levels compared with those with low total homocysteine and CRP concentrations (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raised levels of markers of the acute inflammatory response after stroke are associated with poor outcomes [8]. Extensive studies demonstrated that the peripheral levels of white blood cell (WBC) [911], homocysteine (HCY) [1215], and C-reactive protein [14, 1618] strongly correlate with stroke severity and independently predict mortality and stroke recurrence in acute ischemic stroke patients. However, the effect of these biomarkers on intracranial stenosis is unsubstantial, despite significant attribution of intracranial stenoocclusion to stroke severity.…”
Section: Introductionmentioning
confidence: 99%